Relationship between school culture, sources of leadership efficacy and collective leadership among secondary school teachers in Kuala Lumpur, Malaysia - Sivalingam, Shiveh (2018)
This study examined the relationship between school culture, sources of leadership efficacy and collective leadership among secondary school teachers in the Federal Territory of Kuala Lumpur. It is imperative to determine factors predicting collective leadership among secondary school teachers due to its implications on professionalism in the teaching community. Traditional models of leadership highlight skills and capabilities of an individual but to effectively address the challenges teachers face in schools, we need to move beyond focusing on the individual toward a collective. Studies on collective leadership in the Malaysian context is yet to be done and studying leadership in urban schools under high-accountability conditions measuring the teachers’ ability to cope in extraordinary conditions, is a worthy effort. The theoretical underpinning of this study was established from Rowan’s Conception of Organic Management, Bandura’s Social Cognitive Theory and McClelland’s Human Motivation Theory. This is a descriptive correlational study, conducted in the Federal Territory of Kuala Lumpur, covering districts of Bangsar/Pudu, Sentul and Keramat. The instrument for data collection was a survey in the form of a structured questionnaire, adapted from Leithwood (2012), Usher (2005) and Edward, Gruenert & Valentine (1998) from previously validated studies. A pilot study was conducted on a sample of 30 teachers where an average Cronbach Alpha reliability of 0.7 was obtained on the instrument. In the actual study conducted on 402 teachers, the reliability coefficient ranged from 0.81 to 0.94. The study was analyzed using SPSS version 23. Data was analyzed using descriptive and inferential statistics tabulating mean, standard deviation, percentage, frequencies and Pearson correlation analysis as well as multiple regression, accordingly. This study discovered that the level of collective leadership (M=3.85, SD=0.38), sources of leadership efficacy (M=3.69, SD=0.45) and school culture (M=3.72, SD=0.46) in secondary schools in Kuala Lumpur is high. In addition, sources of leadership efficacy (r = 0.517, p < .01) and school culture (r = 0.538, p< .01) were positively significantly correlated with collective leadership. From the regression analysis, it is was found that both variables were significantly found to predict collective leadership. Since the two variables values are positive, this indicates that there are positive relationships between the variables and outcome, Ŷ = 0.332 x 1 + 0.372 x 2 + 1.672. Results revealed that collective leadership reaffirms the idea that having the influence of many individuals, albeit with different strengths and expertise, will not in any way compromise the initiatives and accountability of teachers, but amplify them. In addition, collective and collaborative ways increased teacher motivation and enhanced job satisfaction which lead to the development of stronger beliefs in the teachers’ own abilities. The findings of this study would inform transpiring policy and practice that inclusion of teachers in leadership roles is pertinent in the element of success in schools.